The Missing Link: The Knowledge Filter and Entrepreneurship in Endogenous Growth - Zoltán J. Ács; David B. Audretsch; Pontus Braunerhjelm; Bo Carlsson (Max Planck Institute for Research into Economic Systems, 2005)
The intellectual breakthrough contributed by the new growth theory was the recognition that investments in knowledge and human capital endogenously generate economic growth through the spillover of knowledge. Endogenous growth theory does not explain how or why spillovers occur. The missing link is the mechanism converting knowledge into economically relevant knowledge. This Paper develops a model that introduces a filter between knowledge and economic knowledge and identifies entrepreneurship as a mechanism that reduces the knowledge filter. A cross-country regression analysis over the period 1981-2001 provides empirical support for the model. We conclude that public policies facilitating knowledge spillovers through entrepreneurship may be an important new approach to promoting economic growth.
Keywords: L10; O10; 330; Endogenous growth; knowledge; innovation and entrepreneurship; Neue Wachstumstheorie; Bildungsinvestition; Spillover-Effekt; Wirtschaftspolitische Wirkungsanalyse; Wirtschaftswachstum; Schätzung; OECD-Staaten